The word of a humble God : the origins, inspiration, and interpretation of scripture - Keen, Karen R., 1973- (Grand Rapids, MI, William B Eerdmans Publishing Company, 2022)
"A concise introduction to the material origins of the Bible, theories of inspiration, and the history of biblical interpretation-with reflections on what this all means for Christians as they read Scripture today"--
""Scripture is a spring of life-giving, life-altering truth, but when we don't understand how and why it came to us, we end up misusing it." How did we get the Bible? And why does it matter? History reveals that Scripture can be used for both life-giving and destructive purposes. Discovering the Bible's origins makes all the difference for fostering redemptive interpretation of Scripture. Bringing together both historical criticism and theology, this investigation examines ancient scribal culture through the lens of faith. What we find is a divine-human collaboration that points to the character of God and the value of human agency. In this concise presentation of a breadth of scholarship usually only found across multiple volumes, Karen Keen offers a vital introduction to the material origins of the Bible, theories of inspiration, and the history of biblical interpretation-with reflections on what this all means for us as we read Scripture today. Through the ins and outs of these important topics, and with the aid of thought-provoking questions and learning activities at the end of each chapter, Keen argues that the Bible and its origins reveal a humble God who invites us to imitate that humility-a humility that is itself the most powerful antidote to the misinterpretation and abuse of Scripture"--
Machine generated contents note: Table of ContentsForeword by Michael Graves -- Introduction -- Part One: The Making of the Bible -- 1. Context: People, Places and Times -- 2. A Community Project -- 3. Dynamic, Not Static -- 4. Bible Variety and Canonization -- Part Two: Inspiration -- 5. God and People Working Together -- 6. The Humility of God and Inspiration -- 7. Does God Speak Literally? -- Part 3: Interpretation -- 8. Interpretive Variety -- 9. Beyond Chronological Snobbery -- 10. Who You Are Matters -- 11. Learning Humility Together.
Includes bibliographical references and indexes.
Keywords: Bible -- History; Bible -- Inspiration; Bible -- Criticism, interpretation, etc; RELIGION / Biblical Criticism & Interpretation / General; RELIGION / Christian Theology / General